2007
DOI: 10.1002/cncr.22759
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive short‐course hepatic arterial infusion chemotherapy with high‐dose 5‐fluorouracil and cisplatin in patients with advanced hepatocellular carcinoma

Abstract: BACKGROUND. Hepatic arterial infusion chemotherapy (HAIC) has often been selected as a therapeutic option for patients with advanced hepatocellular carcinoma (HCC). The objective of the current study was to evaluate the efficacy and safety of repetitive HAIC with high‐dose 5‐fluorouracil (5‐FU) and cisplatin given for 3 days in patients with advanced HCC. METHODS. Between January 2001 and December 2004, a total of 41 patients with unresectable advanced HCC were enrolled. The patients underwent HAIC via the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 17 publications
2
104
1
Order By: Relevance
“…These response and disease control rates are significantly higher than those with sorafenib treatment [5,29] . Several studies reported that the therapeutic effectiveness of HAIC was an important prognostic factor [10,11,30] , which is consistent with our results. In the present study, the median OS of the disease control group after two cycles of HAIC was significantly longer than patients showing PD.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These response and disease control rates are significantly higher than those with sorafenib treatment [5,29] . Several studies reported that the therapeutic effectiveness of HAIC was an important prognostic factor [10,11,30] , which is consistent with our results. In the present study, the median OS of the disease control group after two cycles of HAIC was significantly longer than patients showing PD.…”
Section: Discussionsupporting
confidence: 93%
“…However, the ECF regimen appears to be more toxic than in previous reports of high-dose HAIC [10,14] . While grade 3 hematologic or non-hematologic toxicities comprised less than 5% in previous studies, grade 3 leukopenia, anemia, and thrombocytopenia in this study comprised 8%, 26% and 44% of the toxicities, respectively, and hepatic toxicity was higher.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…These patients included 45 treated with HAIC and 20 treated with sorafenib. All 65 patients had advanced HCC unsuitable for surgical resection, liver transplantation, or nonsurgical interventions [such as radiofrequency ablation or transcatheter arterial chemoembolization (TACE)] because of multiple tumors involving both lobes of the liver or portal invasion in the first or main portal branch (19). Other eligibility criteria included Eastern Cooperative Oncology Group (ECOG) performance status 0 or 1 for sorafenib or 0 to 2 for HAIC, no other serious medical condition, no history of systematic chemotherapy with sorafenib, no concurrent malignancy of another type, and previously described laboratory findings for sorafenib (20).…”
Section: Introductionmentioning
confidence: 99%